IMPLEMENTATION OF RELIGIOUS MODERATION AT BAITUL QUR'AN HIGH SCHOOL YOGYAKARTA - achmad alfaruki (Muta'allim: Jurnal Pendidikan Agama Islam, 2026)
Religious moderation is an essential principle in Islamic education, particularly amidst the growing challenges of intolerance and radicalism. SMA Baitul Qur'an Yogyakarta, as a pesantren-based educational institution, faces the need to instill the values of religious moderation within an environment that integrates formal education and religious development. This study aims to analyze the implementation of religious moderation at SMA Baitul Qur'an Yogyakarta, including the strategies, approaches, and challenges encountered. This research employs a qualitative method with a field study approach. Data were collected through interviews, observations, and documentation. The findings show that values of religious moderation, such as tawassuth (moderation), i’tidal (justice), tasamuh (tolerance), syura (consultation), ishlah (reconciliation), qudwah (role modeling), al-muwathanah (patriotism), al-la ‘unf (non-violence), and i’tiraf al-‘urf (recognition of positive traditions), are implemented through Islamic character education, the habituation of moderation values, role modeling by teachers, and the integration of local Islamic culture. The application of religious moderation in this school is reflected in classroom teaching, extracurricular activities, and daily habits within the pesantren environment. Local traditions that align with Islamic principles are respected and integrated into school activities. Moreover, efforts to prevent intolerant behavior are conducted through persuasive approaches, conflict mediation, and the reinforcement of non-violence attitudes. This implementation creates a harmonious, tolerant, and conducive educational environment, enabling students to grow into moderate, noble individuals who can approach diversity wisely and compassionately.